Nasopharyngeal Bacterial Carriage in the Conjugate Vaccine Era with a Focus on Pneumococci - V. T. Devine; J. M. Jefferies; S. C. Clarke; S. N. Faust (Journal of Immunology Research, 2015)
Seven-valent pneumococcal conjugate vaccine (PCV7) was included in the UK national immunisation program in 2006, and this was replaced by thirteen-valent PCV in 2010. During this time, the carriage of vaccine-type Streptococcus pneumoniae decreased but pneumococcal carriage remained stable due to increases in non-vaccine-type S. pneumoniae. Carriage studies have been undertaken in various countries to monitor vaccine-type replacement and to help predict the serotypes, which may cause invasive disease. There has been less focus on how conjugate vaccines indirectly affect colonization of other nasopharyngeal bacteria. If the nasopharynx is treated as a niche, then bacterial dynamics are accepted to occur. Alterations in these dynamics have been shown due to seasonal changes, antibiotic use, and sibling/day care interaction. It has been shown that, following PCV7 introduction, an eradication of pneumococcal vaccine types has resulted in increases in the abundance of other respiratory pathogens including Haemophilus influenzae and Staphylococcus aureus. These changes are difficult to attribute to PCV7 introduction alone and these studies do not account for further changes due to PCV13 implementation. This review aims to describe nasopharyngeal cocarriage of respiratory pathogens in the PCV era.